Career plateau and career withdrawal intentions among Chinese college physical education teachers - Zhao, Lishan; Zhao, Lina; Zhu, Huaxing; Shang, Xiaoxia; Gu, Cuifeng (Frontiers in Psychology, 2025)
IntroductionExamining factors influencing career withdrawal intentions among university physical education (PE) teachers is crucial because of its effects on teaching quality and the educational environment. We examined the effect of career plateauing among college PE teachers in China on their intentions to leave their profession.MethodA questionnaire survey was conducted with 627 teaching assistants, lecturers, and professors engaged in college PE across Beijing, Tianjin, and Hebei. The underlying mechanisms and boundary conditions were examined, with career satisfaction as a mediating variable and organizational commitment as a moderating variable.ResultsThe findings indicated that career plateaus significantly and positively impact career withdrawal intentions by reducing job satisfaction and motivation to remain in the profession. Job satisfaction partially mediates the relationship between career plateaus and career withdrawal intentions. Furthermore, organizational commitment moderates these relationships, shaping the effect of career plateaus on career withdrawal intentions and mitigating the impact of job satisfaction on career withdrawal intentions.DiscussionThis study provides insights into the effect of career plateauing, which is a common challenge affecting PE teachers’ professional development and strengthening their intentions to leave the organization. The findings can inform strategies to retain educators, enhance teaching effectiveness, and improve student experiences.